FEATURES OF DIRECT DEMOCRACY IN SWITZERLAND: POLITICAL AND LEGAL ANALYSIS - Denysiuk, Svitlana (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2022)
The tools of realization of direct democracy in Switzerland are considered. The Swiss political system, levels of government and distribution of powers between institutions are analyzed. Emphasis is placed on the fact that direct democracy allows the population to directly influence important decisions at all levels. Swiss citizens have the opportunity to vote on their own through a popular initiative and a referendum, which is optional and mandatory. The historical principles of development of instruments of direct democracy are considered. Assumptions are made about possible risks and shortcomings in the process of implementing direct democracy. The point is that extreme right-wing forces may abuse the instruments of democracy to amend existing legislation. The goal is to promote politicians’ own interests. With the help of political technologies, in particular the use of populist slogans, inaccurate statistics and false facts, the leaders of radical parties manipulate the opinion of citizens, inciting them to put forward certain projects to national referendums. The assumption is substantiated that the vote of citizens can lead to the tyranny of the majority. Legislation and responsibility of citizens minimize the risk of such a scenario. The political and legal bases for the use of direct democracy in Switzerland are analyzed. Comparing the advantages and risks of decision-making with such a system, it is concluded that it is optimal for today. The focus of Switzerland’s direct democracy is a compromise dialogue between citizens and the authorities. The draft law «On Local Referendum» № 5512 was considered. Its purpose is to return to the citizens of Ukraine the constitutional right to independently resolve issues of local significance by the territorial community by direct vote. Suggestions for improving the content of this bill have been formulated. We are talking about: the expediency of dividing referendums into types; analysis of the percentage of turnout when considering issues of local importance, increasing the number of questions for voting, etc. It is noted that in order to successfully use the Swiss experience in Ukrainian society, these proposals require broad discussion with the involvement of political scientists and lawyers, awareness of their own responsibility to politicians and the public.